Evaluation of tularaemia courses: a multicentre study from Turkey. (13th August 2014) - Erdem, H.; Ozturk‐Engin, D.; Yesilyurt, M.; Karabay, O.; Elaldi, N.; Celebi, G.; Korkmaz, N.; Guven, T.; Sumer, S.; Tulek, N.; Ural, O.; Yilmaz, G.; et al.
Abstract In this multicentre study, which is the largest case series ever reported, we aimed to describe the features of tularaemia to provide detailed information. We retrospectively included 1034 patients from 41 medical centres. Before the definite diagnosis of tularaemia, tonsillitis (n = 653, 63%) and/or pharyngitis (n = 146, 14%) were the most frequent preliminary diagnoses. The most frequent clinical presentations were oropharyngeal (n = 832, 85.3%), glandular (n = 136, 13.1%) and oculoglandular (n = 105, 10.1%) forms. In 987 patients (95.5%), the lymph nodes were reported to be enlarged, most frequently at the cervical chain jugular (n = 599, 58%), submandibular (n = 401, 39%), and periauricular (n = 55, 5%). Ultrasound imaging showed hyperechoic and hypoechoic patterns (59% and 25%, respectively). Granulomatous inflammation was the most frequent histological finding (56%). The patients were previously given antibiotics for 1176 episodes, mostly with β‐lactam/β‐lactamase inhibitors (n = 793, 76%). Antituberculosis medications were provided in seven (2%) cases. The patients were given rational antibiotics for tularaemia after the start of symptoms, with a mean of 26.8 ± 37.5 days. Treatment failure was considered to have occurred in 495 patients (48%). The most frequent reasons for failure were the production of suppuration in the lymph nodes after the start of treatment (n = 426, 86.1%), the formation of new lymphadenomegalies under treatment (n = 146, 29.5%), and persisting complaints despite 2 weeks of treatment (n = 77, 15.6%). Fine‐needle aspiration was performed in 521 patients (50%) as the most frequent drainage method. In conclusion, tularaemia is a long‐lasting but curable disease in this part of the world. However, the treatment strategy still needs optimization.